Origin and evolution of qingke barley in Tibet. Issue 1 (December 2018) - Zeng, Xingquan; Guo, Yu; Xu, Qijun; Mascher, Martin; Guo, Ganggang; Li, Shuaicheng; Mao, Likai; Liu, Qingfeng; Xia, Zhanfeng; Zhou, Juhong; Yuan, Hongjun; Tai, Shuaishuai; et al.
Abstract Tibetan barley (Hordeum vulgare L., qingke) is the principal cereal cultivated on the Tibetan Plateau for at least 3, 500 years, but its origin and domestication remain unclear. Here, based on deep-coverage whole-genome and published exome-capture resequencing data for a total of 437 accessions, we show that contemporary qingke is derived from eastern domesticated barley and it is introduced to southern Tibet most likely via north Pakistan, India, and Nepal between 4, 500 and 3, 500 years ago. The low genetic diversity of qingke suggests Tibet can be excluded as a center of origin or domestication for barley. The rapid decrease in genetic diversity from eastern domesticated barley to qingke can be explained by a founder effect from 4, 500 to 2, 000 years ago. The haplotypes of the five key domestication genes of barley support a feral or hybridization origin for Tibetan weedy barley and reject the hypothesis of native Tibetan wild barley. The origin of Tibetan barley (qingke) has been a controversial issue for many years. Here, the authors conduct population genomics study to support that qingke is derived from eastern domesticated barley instead of Tibetan wild barley and suggest southern Tibetan Plateau as its introduction route.